Expression Pattern and Immunoregulatory Roles of Galectin-1 and Galectin-3 in Atopic Dermatitis and Psoriasis - Corrêa, Mab P. [UNESP]; Correia-Silva, Rebeca D.; Sasso, Gisela R. Silva; D’Ávila, Solange C. G. P.; Greco, Karin V.; Oliani, Sonia M. [UNESP]; Gil, Cristiane D. [UNESP] (Springer Nature, 2022)
The pathogenesis of atopic dermatitis (AD) and psoriasis (Ps) overlaps, particularly the activation of the immune response and tissue damage. Here, we evaluated galectin (Gal)-1 and Gal-3 levels, which are beta-galactoside-binding proteins with immunomodulatory functions and examined their effects on human keratinocytes stimulated with either interleukin (IL)-4 or IL-17A. Skin biopsies from AD, Ps, and control patients were evaluated using histological and immunohistochemical analyses. Six studies containing publicly available transcriptome data were individually analyzed using the GEO2R tool to detect Gal-1 and Gal-3 mRNA levels. In vitro, IL-4- or IL-17A-stimulated keratinocytes were treated with or without Gal-1 or Gal-3 to evaluate cytokine release and migration. Our findings showed different patterns of expression for Gal-1 and Gal-3 in AD and Ps skins. Densitometric analysis in skin samples showed a marked increase in the protein Gal-1 levels in Ps epidermis and in both AD and Ps dermis compared to controls. Protein and mRNA Gal-3 levels were downregulated in AD and Ps lesional skin compared with the control samples. In vitro, both galectins addition abrogated the release of IL-8 and RANTES in IL-17-stimulated keratinocytes after 24 h, whereas IL-6 release was downregulated by Gal-3 and Gal-1 in IL-4- and IL-17-stimulated cells, respectively. Administration of both galectins also increased the rate of keratinocyte migration under IL-4 or IL-17 stimulation conditions compared with untreated cells. Altogether, the immunoregulatory and migration effects of Gal-1 and Gal-3 on keratinocytes under inflammatory microenvironment make them interesting targets for future therapies in cutaneous diseases. Graphical abstract: [Figure not available: see fulltext.]
Keywords: HaCaT cells; IL-17A; IL-4; inflammation; skin; transcriptome